Exploring the biological impact of bacteria-derived indole compounds on human cell health: Cytotoxicity and cell proliferation across six cell lines - Alisha Janiga-MacNelly; Maddison Vrazel; Ava E. Roat; Maria Teresa Fernandez-Luna; Ramon Lavado (Toxicology Reports)
Over the past two decades, research has increasingly focused on the interactions between diet, gut microbiota, and host organisms. Recent evidence suggests that tryptophan, an essential amino acid, can be metabolized by gut microbiota into indoles, which have significant biological effects. However, most research is limited to indole and its liver metabolite, indoxyl sulfate. This study examines the cytotoxic effects of five indole derivatives — indole-3-carboxylic acid (I3CA), indole-3-aldehyde (I3A), indole-3-acetic acid (IAA), indole-3-propionic acid (IPA), and 3-methylindole (skatole, 3-MI) — on six human cell lines: adipose-derived mesenchymal stem cells (MSC), hepatocellular carcinoma (HepG2), liver progenitor cells (HepaRG), colorectal carcinoma cells (Caco-2), breast cancer cells (T47D), and lung fibroblast (MRC-5). Results show no sensitivity to indole itself across cell lines. MRC-5 was sensitive to all other compounds (EC50 0.52–49.8 µM). MSCs responded to IPA, I3CA, I3A, and 3-MI (EC50 0.33–1.87 µM), while HepaRG cells were affected by IAA, I3CA, I3A, and 3-MI (EC50 1.98–66.4 µM). T47D cells were sensitive to IPA and IAA, and Caco-2 cells only to IAA (EC50 2.02, 1.68, 0.52 µM, respectively). HepG2 cells showed no change in viability. AhR activation in HepG2-AhR-Lucia cells was triggered by all derivatives, particularly I3A, IPA, and I3CA. Growth experiments revealed I3CA decreased Caco-2 proliferation while increasing T47D proliferation. The findings suggest indole derivatives are generally non-cytotoxic to carcinomas but may adversely affect stem cells, with effects varying across cell lines.